Preoperative sonography efficacy for cholecystoscopy cannula orientation, evaluation on pigs (Revista Argentina de Cirugía, 2021)
Background: the Cholecystoscopic Cholecystosclerosis is a single session procedure, under enhancing process, which pursues a definitive Gallbladder elimination by means of stone removal and mucous membrane ablation through Operatory Cholecystoscopy, under local-regional anesthesia, and requires the insertion of a Cholecistoscopy Cannula from the abdominal wall toward the gallbladder fundus.Objective: to assess the effectiveness of the Preoperative Sonography when it comes to finding the right place for the Cholecystoscopy Cannula insertion. It is important to achieve the Cholecystoscopy Cannula being introduced in a way that its axis matches the Gallbladder´s axis, in order to provide a suitable passage for instruments between the Cannula and the Gallbladder´s lumen.Material and Method: preoperative sonography was planned to be performed in a series of surgical interventions on pigs, in order to determine the position of the gallbladder in its three spatial dimensions, allowing a virtual projection of the organ´s axis toward the abdominal wall, thus pointing to the most suitable place for the Cholecystoscopy Cannula insertion.Results: five procedures were performed as planned, the Cholecystoscopy Cannula rapidly reached the gallbladder fundus and coincidence between cannula axis and gallbladder axis was achieved in all the cases.Conclusions: preoperative sonography seems to be very efficient for choosing the right place for Cholecystoscopy Cannula insertion accordingly to this experience.
Keywords: gallbladder; sclerosis; sonography; endoscopy; cholecystoscopy